Ionosphere Influenced From Lower-Lying Atmospheric Regions - Koucká Knížová, Petra; Laštovička, Jan; Kouba, Daniel; Mošna, Zbyšek; Podolská, Katerina; Potužníková, Katerina; Šindelářová, Tereza; Chum, Jaroslav; Rusz, Jan (Frontiers in Astronomy and Space Sciences, 2021)
The ionosphere represents part of the upper atmosphere. Its variability is observed on a wide-scale temporal range from minutes, or even shorter, up to scales of the solar cycle and secular variations of solar energy input. Ionosphere behavior is predominantly determined by solar and geomagnetic forcing. However, the lower-laying atmospheric regions can contribute significantly to the resulting energy budget. The energy transfer between distant atmospheric parts happens due to atmospheric waves that propagate from their source region up to ionospheric heights. Experimental observations show the importance of involvement of the lower atmosphere in ionospheric variability studies in order to accurately capture smaller-scale features of the upper atmosphere. The first part of the paper provides a brief overview of the lower atmosphere influence on the ionosphere and summarizes the current knowledge. In the second part, we demonstrate experimental evidence from mid-latitudes, particularly those based on observations by instruments operated by the Institute of Atmospheric Physics, Czech Academy of Sciences. The focus will mainly be on coupling by atmospheric waves.